Joint-specific DNA methylation and transcriptome signatures in rheumatoid arthritis identify distinct pathogenic processes - Rizi Ai (Nature Portfolio, 2016)
Rheumatoid arthritis is an inflammatory disease that selectively affects different joints. Here the authors show that gene expression and DNA methylation patterns of fibroblast-like synoviocytes differ between hip and knee joints in patients with RA, thus providing epigenetic and transcriptomic evidence for this anatomic selectivity of inflammation.